22. MICROBIAL AGENTS IN CHILDREN WITH PNEUMONIA AT THE PEDIATRIC DEPARTMENT - BACH MAI HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2023)
Pneumonia is the disease with the highest mortality rate among infectious diseases. Identifyingthe cause of the disease helps to make treatment more effective and limit antibiotic resistance.Research objective: To identify the microbial pathogens causing pneumonia in children at thePediatrics Department - Bach Mai Hospital in 2021. Methodology: A retrospective review of allinpatient pneumonia treatment records at the department of Pediatrics - Bach Mai Hospital, agefrom 0 months to 15 years old, meeting the criteria for definite diagnosis of pneumonia and havingperformed microbiological testing of nasopharyngeal swab samples satisfying the selection criteriaand to exclude, to expel. Results: Through the results of a study of 208 pneumonia cases that metthe access standards at the Pediatrics Department, Bach Mai Hospital in 2021, the detection rate ofmicrobiological etiology was 50.8%, in which the microbial etiology was bacteria accounted for44.0%; co-infection with 2 or more bacteria accounted for 6.7%. No viral or fungal etiology wasdetected. Among bacterial etiologies, 83.0% are typical bacteria, and atypical bacteria account for3.0%. The most common bacteria groups were H. influenzae (51.9%), S. pneumoniae (24.6%) andM. catarrhalis (8.2%). Conclusion: The main cause of pneumonia in children is microbiological, inwhich mainly typical bacteria.
Keywords: Pediatric pneumonia, microbiology, Department of Pediatrics-Bach Mai.